Electrochemical and Morphological Investigations of Ga Addition to Pt Electrocatalyst Supported on Carbon. (29th March 2017) - Paganoto, Giordano T.; Santos, Deise M.; Evangelista, Tereza C. S.; Guimarães, Marco C. C.; Carneiro, Maria Tereza W. D.; Ribeiro, Josimar
Abstract : This paper is consisted in the synthesis of platinum-based electrocatalysts supported on carbon (Vulcan XC-72) and investigation of the addition of gallium in their physicochemical and electrochemical properties toward ethanol oxidation reaction (EOR). PtGa/C electrocatalysts were prepared through thermal decomposition of polymeric precursor method at a temperature of 350°C. Six different compositions were homemade: Pt50 Ga50 /C, Pt60 Ga40 /C, Pt70 Ga30 /C, Pt80 Ga20 /C, Pt90 Ga10 /C, and Pt100 /C. These electrocatalysts were electrochemically characterized by cyclic voltammetry (CV), chronoamperometry (CA), chronopotentiometry (CP), and electrochemical impedance spectroscopy (EIS) in the presence and absence of ethanol 1.0 mol L −1 . Thermogravimetric analysis (TGA), energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), and transmission electron microscopy (TEM) were also carried out for a physicochemical characterization of those materials. XRD results showed the main peaks of face-centered cubic Pt. The particle sizes obtained from XRD and TEM analysis range from 7.2 nm to 12.9 nm. The CV results indicate behavior typical of Pt-based electrocatalysts in acid medium. The CV, EIS, and CA data reveal that the addition of up to 31% of gallium to the Pt highly improves catalytic activity on EOR response when compared to Pt100 /C.